Factors associated with central obesity among university workers in Syarif Hidayatullah State Islamic University Jakarta - Yustiyani Yustiyani; Iqbal Nurmansyah Mochamad; Febrianti Febrianti (BIO Web of Conferences)
Central obesity poses a greater risk than general obesity. The global prevalence of obesity is increasing, including in Indonesia. The incidence of central obesity is associated with several factors, including sociodemographic status and physical activity levels. This study aims to investigate the association between sociodemographic status and physical activity level with central obesity. This study employed a cross-sectional study involving 111 adults aged 18-59 in South Tangerang City, Indonesia. Sociodemographic factors included age, sex, educational level, family size, and marital status. Physical activity levels were assessed using International Physical Activity Questionnaire (IPAQ). Both sociodemographic status and physical activity data were collected through interviews. The waist circumference was measured using inelastic tape. More than half of the respondents (57.63%) were centrally obese. Sex, marital status, educational level, and physical activity were significantly associated with central obesity (p-value < 0.05). Female (OR 3.639), married (OR 3.381), and less active (OR 2.746) respondents were more likely to have central obesity. A low educational level was found to be protective against central obesity (OR 0.285). Females, individuals with high education level, and married individuals are advised to be physically active to prevent the central obesity.